Surprise and Breaking the Horizon of Expectations (Ziad Bin Abeeh’s Speech in Al-Basra as an Applied Model) - Basal, Mohammad; Fayyad, Aksum (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This research paper presents a number of attempts in order to clarify the concept of "surprise and breaking the horizon of expectations" .It also tends to present the mechanism for applying this concept to the historical text which is not directly realated to the modern theories of linguistics. It’s very clear that both sides of the concept the theoretical side, and the partical one in Ziad Bin Abeeh’s speech in AL-Basra as an applied model, belong to two totally different fields of knowledge. We notice this concept with Ziad Bin Abeeh’s at the very first word of his speech, where he overlooked starting with the Basemla, overriding, Thus, the protocols of discourse openings , as if he were proceeding a text or a precedent act of speech. At this particular point, the practical side begins to observe the concept of expectation in speech based on the data introduced in modern linguistics in reception theory and pragmatics through the concepts of inference and reasoning , and the act of speech and intentionality, etc..In addition to that, the textual analysis connects the implications of these concepts within the linguistic textual structure, and its relation with breaking the horizon of expectation, and to what extent it affects , the discourse act and its resulting act. Thus, pragmaticcs, which is the branch of linguistics dealing with language in use seem to be the best approach to the analysis of Ziad’s speech and figuring out its effects on the recipient.